Beyond jihad : the pacifist tradition in West African Islam - Sanneh, Lamin O. (2016)
"Over the course of the last 1400 years, Islam has grown from a small band of followers on the Arabian peninsula into a global religion of over a billion believers. How did this happen? The usual answer is that Islam spread by the sword-believers waged jihad against rival tribes and kingdoms and forced them to convert. Lamin Sanneh argues that this is far from the whole story. Beyond Jihad examines the origin and evolution of the African pacifist tradition in Islam, beginning with an inquiry into the faith's origins and expansion in North Africa and its transmission across trans-Saharan trade routes to West Africa. The book focuses on the ways in which, without jihad, the religion spread and took hold, and what that tells us about the nature of religious and social change. At the heart of this process were clerics who used religious and legal scholarship to promote Islam. Once this clerical class emerged, it offered continuity and stability in the midst of political changes and cultural shifts, helping to inhibit the spread of radicalism, and subduing the urge to wage jihad. With its policy of religious and inter-ethnic accommodation, this pacifist tradition took Islam beyond traditional trade routes and kingdoms into remote districts of the Mali Empire, instilling a patient, Sufi-inspired, and jihad-negating impulse into religious life and practice. Islam was successful in Africa, Sanneh argues, not because of military might but because it was made African by Africans who adapted it to a variety of contexts."--Book jacket
Beyond North Africa: synthesis and transmission -- Beyond the veil : the Almoravids and Ghana -- Beyond desert trails : religion and social change -- Beyond routes and kingdoms : new frontiers, old hinterlands -- Beyond trade and markets : community and vocation -- Beyond homeland : religious formation and expansion -- Beyond tribe and tongue in Futa Jallon : religion and ethnicity -- Beyond consolidation : rejuvenating the heritage -- Beyond confrontation and crisis : colonial denouement -- Beyond confinement : mobile cells and the clerical web -- Beyond consensus : a house divided -- Beyond Jihad : champions and opponents -- Beyond politics : comparative perspectives -- End of Jihad?: tradition and continuity
Includes bibliographical references (pages 319-338) and index
Keywords: Islam -- Africa, West; Islam -- Relations; Pacifism -- Religious aspects -- Islam